The use of anti-hyperlipidemia in a private hospital in Yogyakarta during 2013-2019 - Yosi Febrianti; Saepudin Saepudin; Dian Medisa; Haryo Tetuko; Siti Nurul Fadhillah Hasanah (Jurnal Ilmiah Farmasi, 2021)
Background: Lipid modifying agents have an important role in the primary and secondary prevention of cardiovascular diseases such as coronary heart disease and stroke. The use of lipid-modifying agents tends to increase along with the increasing prevalence of these diseases.Objectives: To determine the utilization of lipid modifying agents for hospitalized patients in a private hospital in Yogyakarta during the period of 2013 - 2019 in regard to the agents used and their quantity.Methods: The main data for this study were aggregate data on the use of lipid modifying agents for hospitalized patients during 2013-2019 obtained from the hospital pharmacy department. After identification of the names of lipid modifying agents, the quantities of these drugs were then calculated in units of defined daily dose (DDD) and the final quantity was expressed in DDD/100 bed days (BD). The R2 value from linear regression was used to determine the trend of use of individual agents over the period.Results: There were two pharmacological subgroups of lipid modifying agents used during the period of 2013 – 2019 with an average of total quantity of 14.81 DDD/100 BD. Utilization of statins was approximately 90% of the total use, and utilization of fibrates tended to decrease over the period. Individually, simvastatin use decreased significantly over the period (R2 = 0.885), but atorvastatin use continued to increase (R2 = 0.908) with 10-fold increase from 2013 to 2019.Conclusion: The lipid modifying agents used during the period 2013 - 2019 were predominantly statins, and the utilization of atorvastatin increased significantly during this period.Keywords: lipid modifying agents, ATC/DDD, fibrates, statinsIntisariLatar Belakang: Antihiperlipidemia memiliki peran penting dalam pencegahan primer maupun sekunder penyakit kardiovaskular terutama penyakit jantung koroner dan stroke. Penggunaan golongan obat tersebut di berbagai fasilitas kesehatan cukup tinggi seiring dengan masih tingginya prevalensi penyakit kardiovaskular.Tujuan: Untuk mengetahui profil penggunaan antihiperlipidemia untuk pasien rawat inap di salah satu rumah sakit swasta di Yogyakarta selama periode tahun 2013 – 2019 berdasarkan jenis obat dan kuantitas penggunaannya.Metode: Data utama yang digunakan dalam penelitian ini adalah data agregat penggunaan antihiperlipidemia untuk pasien rawat inap selama tahun 2013 - 2019 yang diperoleh dari instalasi farmasi rumah sakit. Setelah mengetahui jenis obat antihiperlipidemia yang digunakan, kuantitas penggunaan obat-obat tersebut dihitung dalam satuan defined daily dose (DDD) dan kuantitas akhir dinyatakan dalam DDD/100 bed days (BD). Nilai R2 dari persamaan garis lurus digunakan untuk mengetahui kecenderungan peningkatan atau penurunan penggunaan obat antihiperlipidemia secara individual selama periode tahun 2013 – 2019.Hasil: Terdapat dua golongan antihiperlipidemia yang digunakan selama periode tahun 2013 – 2019, yaitu golongan statin dan fibrat, dengan rata-rata kuantitas penggunaan secara total sebesar 14,81 DDD/100 BD. Penggunaan antihiperlipidemia golongan statin secara rata-rata sekitar 90% dari keseluruhan antihiperlipidemia yang digunakan dan penggunaan obat golongan fibrat cenderung menurun dari tahun ke tahun. Secara individual, simvastatin menunjukkan penggunaan yang menurun secara signifikan dari tahun ke tahun (R2=0,885) namun sebaliknya penggunaan atorvastatin terus meningkat (R2=0,908) dengan peningkatan hampir 10 kali lipat dari tahun 2013 ke tahun 2019.Kesimpulan: Antihiperlipidemia yang digunakan selama periode tahun 2013 – 2019 sebagian besar merupakan golongan statin dan atorvastatin yang penggunaannya yang meningkat secara signifikan.Kata kunci: antihiperlipidemia, ATC/DDD, fibrat, statin